An overview of research topics and focuses of the empirical MOOC literature / Rasheed Abubakar Rasheed ... [et al.] - Rasheed, Rasheed Abubakar; Kamsin, Amirrudin; Abdullah, Nor Aniza; Zakari, Abubakar; Maitama, Jaafar Zubairu (UiTM Press, 2020)
Over the years, MOOCs have been an attractive research area and has yielded large quantities of empirical and review studies. However, existing review studies in MOOCs are characterized by short year coverage or focusing on a specific theme. Therefore, we aim to examine the overall research topics, focuses and research productivity of the empirical MOOC literature from 2009 to 2018. Findings show that research in MOOCs have risen significantly since 2013. MOOC studies have mostly focused on learners' completion/dropout, and other learner dropout related topics. Specific types of learners' self-regulation themes in MOOCs were not researched.